The marking of reported discourse in medieval French manuscripts - Marnette, S (2006)
This article studies how reported speech is marked in medieval texts both visually for the reader of manuscripts and orally for the listener (medieval texts being sung, recited or in any case read aloud). It examines morpho-syntactic, discursive and lexical marking as well as prosody and it pays particular attention to manuscript punctuation, a field that is still very much understudied at the moment. The study takes into account the type of text envisaged (e.g. verse or prose, chanson de geste versus romance, etc.) and their period (from 12th to 15th century).